CASE REPORT – ACUPUNCTURE TREATMENT IN FEMALE PATIENT PRESENTED WITH PRIMARY HYPOTHYROIDISM - Arsovska, Blagica; Zhu, Jihe; Kozovska, Kristina (International Journal of Research -GRANTHAALAYAH, 2020)
Primary hypothyroidism occurs due to increased thyroid-stimulating hormone (TSH). Most commonly it’s autoimmune and results from Hashimoto’s thyroiditis, which is also often associated with a firm goiter. In the primary hypothyroidism, the thyroid is being stimulated properly, but it’s not able to produce enough thyroid hormones so the body can function normally. This means that the source of the problem is the thyroid itself. In this research is presented a case of a 33 year old woman diagnosed with primary hypothyroidism. The patient has done 34 acupuncture treatments in a period of 8 months. After 6 months of starting the treatment the patient medicament therapy with Euthirox was ended. The anti-TPO levels were decreased from 425 to 70.3 IU/ml and the TSH and fT4 levels were effectively kept within the normal range. Acupuncture treatment as part of the Traditional Chinese Medicine can be exceptionally effective in the treatment of primary hypothyroidism, although as a treatment for autoimmune disease it takes more time to see the positive results. Considering that it is an autoimmune and chronic disease, treatment also requires a long-term approach. The patient’s condition will be monitored and treatments will be continued until complete normalization of the anti-TPO levels.